Student Character Education Towards Excellence: Optimization of Transformational Leadership of Lecturers - Situmorang, Meditatio; Situmeang, Chintya Megaria (LP. Ma'arif Janggan Magetan, 2022)
Lecturers as educators have a very large role in determining the quality of higher education graduates. Transformational leadership becomes a leadership style that can be used by lecturers to direct and guide students to have superior character. lecturers who teach in the Christian Leadership Department have implemented this transformational leadership, although it has not been implemented thoroughly. Furthermore, problems arise about the application of transformational leadership of lecturers that have not been maximized, making students not have a truly superior character. This research was conducted to find out how lecturers apply transformational leadership and how it affects the students of the Christian Leadership Department? This research will examine students in the Christian Leadership Department, Faculty of Theological Sciences IAKN Tarutung about the application of transformational leadership of lecturers and their influence in shaping student character. Through this research, it is hoped that lecturers can apply transformational leadership optimally, because the transformational leadership applied by lecturers is influential in building superior student character. Through the application of transformational leadership, students experience changes and have superior character.